US Position on Kurdish Issue in Southern Kurdistan (1980-1988): A Historical-Political Research - Khaleel Ali murad; Nihro Mohammed Abulqader (QALAAI ZANIST JOURNAL, 2020)
Following the demise of Kurdish revolution in 1975, the US turned their back on the Kurds completely. Kurds became hopeless and were shocked because they had pinned much hopes on them. This rigorous stance from the US angered Kurds as a whole. Therefore, those parties who came into existence after 1975 pursued some sort of anti American slogans believing that the US betrayed Kurds. The US repeatedly made it clear that the Kurdish issue was a domestic issue of Iraq. Kurds trying to enjoy close relations with the US was absolutely unilateral. The Iran-Iraq war paved the way for Iraq to forge relationships with the US to the degree they even received arms and intelligence information from Washington. With time passing Iraq played the role of distancing Kurds from the US. Following the ‘Enemy of my Enemy is my Friend’ the US paved the way for Kurds to get close to Iran, a move which angered Washington. Due to their interests and policies, the US turned a blind eye on Baath regime’s repressive acts against Kurds including the use of chemical weapons against Kurds in 1988 in the city of Halabja which claimed the lives of 5000 civilians and wounded 10000 more, the notorious Anfal genocide campaign and the destruction of thousands of Kurdish villages. There was, however, a degree of differences in stance between the then US administration and the Congress. Though the Congress and House of Representatives took a set of measures against the Baath regime, the US administration objected them. Following the end of Iraq-Iran war, the situation changed to some extent as the US media and Congress appeared to speak louder against the use of chemical weapons against Kurds. The US started to put an end to their supports to Saddam due to regional and global developments, yet the Kurds were not part of their agenda.